Editorial - PPGAC, Revista Cena (Cena, 2016)
<span style="color: #000000; font-family: ’Times New Roman’; font-size: medium; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: normal; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; display: inline !important; float: none;">Is the contemporary scene, contaminated by the art of performance, by the precepts of the post-dramatic and the performative, by the somatic practices, and by an explosion of possibilities of non-representation on the scene, still holding the idea of training? In this dossier, we propose the discussion on to which extent bodily practices today still follow principles previously worked systematically in the training of director-pedagogues of the twentieth century. What did remain of this notion so impregnated in the scenic making of the last century?